New species of the aphid parasitoids of the genus Binodoxys Mackauer (Hymenoptera: Braconidae: Aphidiinae) from the fauna of Russia - Davidian, Elena M.; Belokobylskij, Sergey A. (Zootaxa, 2022)
The descriptions of two new species from the genus Binodoxys Mackauer characterised by short prongs on the posterior margin of the last metasomal sternite are provided from the north-western territory of the European part and Eastern Siberia of Russia. Binodoxys crataegi sp. nov. was reared from the aphid Aphis pomi De Geer, 1773 on Crataegus sp. in the St. Petersburg region, but B. ekaterinaе sp. nov. was collected by net in Irkutsk Province, near Baikal Lake, and the host is unknown.